Impacts of Acute Hypoxia on Alzheimer's Disease-Like Pathologies in APPswe/PS1dE9 Mice and Their Wild Type Littermates - Zhang, Feng; Zhong, Rujia; Qi, Hongqian; Li, Song; Cheng, Cheng; Liu, Xinyao; Liu, Yufei; Le, Weidong (Frontiers in Neuroscience, 2018)
Alzheimer's disease (AD) is the most common form of dementia and pathologically featured by β-amyloid (Aβ) plaque deposition and hyper-phosphorylated tau aggregation in the brain. Environmental factors are believed to contribute to the pathogenesis and progression of AD. In the present study, we investigated the impacts of acute hypoxia on Aβ and tau pathologies, neuroinflammation, mitochondrial function, and autophagy in APPswe/PS1dE9 AD mouse model. Male APPswe/PS1dE9 transgenic (Tg) mice and their age-matched wild type (Wt) littermates were exposed to one single acute hypoxic episode (oxygen 7%) for 24 h. We found that acute hypoxia exposure increased the expressions of amyloid precursor protein (APP), anterior pharynx-defective 1 (APH1) and cyclin-dependent kinase 5 (CDK5), and promoted tau phosphorylation at T181 and T231 residues in both Tg and Wt mice. In addition, acute hypoxia also induced autophagy through the mammalian target of rapamycin (mTOR) signaling, elicited abnormal mitochondrial function and neuroinflammation in both Tg and Wt mice. In summary, all these findings suggest that acute hypoxia could induce the AD-like pathological damages in the brain of APPswe/PS1dE9 mice and Wt mice to some extent.